Positions of English and Tagalog adjectives and adverbs in utterances a contrastive analysis - Morales, Caridad Pangilinan 1933- (s.n.], 1972)
This paper attempted to describe and contrast the order of English and Tagalog adjectives and adverbs in utterance. It shows that according to form, English adjectibes are of two kinds, as stated by Nelson Francis in the book, The Structure of American English. Tagalog has certain compound adjective constructions not commonly found in English. Both languages are movable but Tagalog is more movable.